Hubungan Kedisiplinan Kerja Dan Inovasi Pembelajaran Dengan Kinerja Dosen Perguruan Tinggi Keagamaan Buddha - Wijani Wijani; Alexander Candra (Dhammavicaya : Jurnal Pengkajian Dhamma, 2021)
Educator performance is an important element in education, besides that, it is also a determinant of the level of education quality. Good discipline reflects a person's sense of responsibility for the tasks assigned to him. This study aims to determine there is a relationship between work discipline and lecturer performance in Buddhist religious colleges. (2) There is a Relationship between Learning Innovation and Lecturer Performance in Buddhist Religious Universities. The population in this study were Lecturers at the Budda Religious College. The number of samples was 60 respondents. The activity counter uses SPSS version 26 software. Multiple linear regression analysis is a method used to analyze the data in this study. The results showed that work discipline and lecturer welfare had a positive and significant effect on lecturer performance by 0.714 (75%) which was the value of R Square and the remaining 25% was influenced by other variables in this study.